Going against the flow: Motivations of professionals with critical views on vaccination - Elisha Ety; Guetzkow Josh; Shir-Raz Yaffa; Ronel Natti (Temida, 2022)
T he controversy over vaccines has persisted since their introduction in the eighteenth century. While many studies have addressed the concerns and motivations of the general population regarding hesitation and resistance to vaccination (especially parents, concerning routine childhood immunization), the present study was designed to examine this issue among professionals from a victimological perspective, thus its uniqueness. Study participants were researchers and practitioners involved with vaccines who hold a critical position on vaccines and their ways of dealing with what they perceived as suppression of dissent in the field of vaccination. The motivations identified among the researchers and practitioners in our study referred to ethical aspects of professional obligation to patients, patient rights, freedom of choice, and lack of trust in the medical establishment. The participants also perceived themselves as victims of suppressive tactics due to their critical position, to which they responded in two contrasting ways: continuing to dissent while insisting on their right to have their voices heard or abandoning their public dissent due to the reactions and repercussions they faced. The article discusses the implications of these findings in the context of scientific integrity, violation of democratic and ethical values, freedom of speech, and its impact on the public’s trust in science and medicine.